THE NUCLEAR ENERGY FACTOR IN INDIAN POLITICS - A. A. Boyko (MGIMO University Press, 2017)
Nuclear energy is a key branch of the world power system. The nuclear energy development is viewed by India as one of the ways to resolve the problem of the energy supply. In 2008 the country gained more opportunities for developing nuclear power sector and solving the national power deficit problem after NSG lifted restrictions on nuclear trade. This resulted in foreign companies emerging on the Indian nuclear market. In 2011 after the major emergency at Fukushima Daiichi Nuclear Power Plant in Japan India faced numerous anti-nuclear protests backed by NGOs, including those with foreign funding, and political parties. The article deals with the question of the political role this anti-nuclear opposition plays in India. According to some researchers the protests are organized by the competitors in order to compromise the business of a Russian company Rosatom in India. However, such demonstrations are spread throughout the country and directed against the competitors of Rosatom as well. The article comes to conclusion that the protests are just a reflection of the political fights in India where nuclear energy is a significant political factor.